Efektivitas Belajar Siswa Kelas XI pada Semester Juli - Desember Tahun 2021 di MAN 3 Payakumbuh - Anugrah, Diko Fajar; Surtani, Surtani (ALSYS, 2024)
This research to eval_uate the effectiveness of the learning process at MAN 3 Payakumbuh during the COVID-19 pandemic, especially after the implementation of the face-to-face learning policy in November 2020. The research method used is quantitative descriptive by analyzing data on time allocation, effectiveness of assignment work, and student exam result. The research results show that the allocation of study time is in the effective category (80%), but there are 20% that are not optimal. The effectiveness of completing assignments is also effective (80%), with 20% of students showing low performance. Meanwhile, the effectiveness of exam results is in the effective category (70%), even though 30% of students experience difficulties. The findings of this study highlight the need for improved time management, student engagement, and understanding of the material to achieve better learning effectiveness.